Method Development and Validation of Stability-Indicating HPLC-UV Method for Determination of 5 -Fluorouracil - Gulati, Diksha; Arora, Deepshi; Taneja, Yugam; Dhingra, Ashwani (Current Spectroscopy and Chromatography, 2024)
IntroductionIn the realm of pharmaceutical analysis, the development and validation of a High-Performance Liquid Chromatography with Ultraviolet Detection (HPLC-UV) method for the precise determination of 5-FU stand as a crucial endeavor.MethodsThis study outlines the systematic process of method development, optimization, and subsequent validation to ensure the reliability and applicability of the method in pharmaceutical quality control. Method optimization included the selection of an appropriate stationary phase, mobile phase composition, and chromatographic conditions to achieve optimum resolution, sensitivity, and run time.ResultsA speedy, simple, and dependable HPLC technique for quantifying 5-FU on a C18 (250 4.6 mm, 5 m particle size) column with solvent A included 10 mM phosphate buffer with pH 3.0 and solvent B with acetonitrile as the mobile phase. At 250 nm, the effluent was measured. Further, 5-FU had a retention time of 1.698 minutes.ConclusionAccording to ICH criteria, the devised technique was validated for precision, accuracy, linearity range, robustness, and ruggedness.
Keywords: linearity